Accessing behavioral health care during COVID: rapid transition from in-person to teleconferencing medical group visits. (February 2021) - Juarez-Reyes, Maria; Mui, Heather Z.; Kling, Samantha M.R.; Brown-Johnson, Cati
Background and aim: Effective and safe behavioral health interventions in primary care are critical during pandemic and other disaster situations. California shelter-in-place orders necessitated rapid transition of an effective mindfulness-based medical group visit (MGV) program from in-person to videoconferenced sessions (VCSs). Aim: to Describe procedures, acceptability, and feasibility of converting from in-person to VCS. Patients and methods: Methods: qualitative. Dataset: primary care. Intervention: a six-session 2-h MGV program with educational and mindfulness components was converted. Four in-person sessions and two VCSs were held. General Anxiety Disorder and Patient Health Questionnaire-9 were administered at first and last sessions. A semi-structured focus group was conducted after session six. Population studied: six primary care patients (42 ± 11 years) with stress, anxiety, or depression participated. Results: Procedural changes included remote material distribution, scheduling, hosting, and facilitation functions using the Zoom platform. The focus group revealed that patients preferred in-person sessions during initial visits, but appreciated transitioning to VCS, which provided continued support during a challenging time. Instruction on technical (e.g. logging on) and social (e.g. signaling next speaker) aspects of VCS was suggested. Building relationships through conversations was an important part before and after in-person sessions missing from VCS. Patients suggested combining in-person and VCS to allow relationship building while also improving access. Conclusion: While many procedural changes were needed to facilitate conversion to VCS, primary care patients seeking stress, anxiety, and depression interventions found VCS acceptable during COVID-19. Future iterations of this program are proposed which incorporate procedural changes and facilitate relationship building between patients in VCS.